Globalisation is not spelt with a zed: Geography texts for and from Oceania. Issue 1 (7th December 2017) - Murray, Warwick E.; Overton, John
Abstract : Writing on a subject as all‐encompassing as globalisation from "down here" (Oceania) in a way that is relevant "up there" (Anglo‐America), while retaining the "Antipodean" perspectives we seek to represent and embody, presents significant tensions. How does a textbook on globalisation written from our viewpoint negotiate the very system it aims to critique? We reflect on writing Geographies of globalization in the context of the fraught politics and challenging logistics of writing human geographies in New Zealand and the Antipodes generally.